Pertumbuhan Jagung (Zea mays L). dengan Pemberian Glomus aggregatum dan Biofertilizer pada Tanah Bekas Penambangan Emas - Mukarlina, Desi Leskona, Riza Linda, (Jurnal Protobiont, 2013)
Gold mining activity caused damage to the soil as soil microbial populations, flora and fauna destruction, mercury content and tailling.using biofertilizer and mychorrizal are needed for corn growth ( Zea mays L). The research study was conducted from July 2012 to August 2012 used Complete Randomized Design (CRP) with two factor. The first factor was Glomus aggregatum with four level treatments; 0 g/polybag, 10 g/polybag, 20 g/polybag and 30 g/polybag. The second factor was biofertilizer with four level treatments that are; 0 ml/plant, 16 ml/plant, 32 ml/plant and 48 ml/plant. Each treatment was repeated three times with 48 unit experiments. The research finding showed that Glomus aggregatum 20 g/polybag gave the highest tall for plant height (69. 41 cm), fresh plant weight ( 51. 39 g), and dried plant weight (7.14 g). Giving biofertilizer 48 ml/plant produced the highest number of leaves (11.00 leaves). The interaction between biofertilizer 48 ml/plant and Glomus aggregatum 30 g/polybag showed the highest infection (7.14 %).